Educating for Peace: The Role and Impact of International Organisations in Interwar and Post-War Danish School Experiments, 1918–1975 - Andreasen, Karen Egedal; Ydesen, Christian (Nordic Journal of Educational History, 2015)
In the aftermath of the two world wars, strong international networks and organisations manifested themselves with promotion of peace through education on their agenda. Danish pedagogical experiments and experimental schools were strongly influenced by these trends and played a role in subsequent school practices and policies. Drawing on the notions of “the transnational” and “trading spaces” as well as the theoretical concepts of transfer, translation, and transformation, this article addresses the following research question: How were international ideas, knowledge and practice of promoting peace through education transferred, translated, and transformed in Danish school experiments in interwar and post-war scenarios? In exploring this question, the article uses transnational and Danish archival sources as well as journals and reports linked to the Danish progressive education movement. Thus, the article contributes to our understanding of the entanglements of educational ideas and to how trends of internationalisation and globalisation work.